PENGARUH STOCK SPLIT TERHADAP LIKUIDITAS PERDAGANGAN SAHAM PADA PERUSAHAAN GO PUBLIK DI BURSA EFEK INDONESIA - admin, Harisa Prafitri B11110007 (Jurnal Manajemen Update, 2016)
The objective of this research is to examine the effect ofÂ  stock split on liquidity of stock for company that listed in Indonesia stock exchange (BEI) from 2008-2013. This research is a quantitative research with a sample of 43 selected company by using purposive sampling technique. Data is then analized by using simple regression analysis. The results of the analysis show that the stock split has not an effect on stock liquidity. Based on this research, the company shouldnot get too focused on the events of the stock split. but how do the companyâ€™s performance could be increased after the stock split so that investors can trust that the company will provide good prospects for the future. Key Words: Stock Split and Trading Volume